Answer: The log simplifies to
-2-------------------------------------------
-------------------------------------------
Explanation:
We will use the log rule that log(x^y) = y*log(x). Call this log rule 1. This log rule basically allows us to pull the exponent down.
Another log rule that we will use is
![\log_x\left(x\right) = 1](https://tex.z-dn.net/?f=%5Clog_x%5Cleft%28x%5Cright%29%20%3D%201)
where x is any positive real number but x = 1 is NOT allowed. Call this log rule 2.
Because 36 = 6^2, this means that 1/36 = 6^(-2)
-------------
So,
![\log_6\left(\frac{1}{36}\right)=\log_6\left(\frac{1}{6^2}\right)](https://tex.z-dn.net/?f=%5Clog_6%5Cleft%28%5Cfrac%7B1%7D%7B36%7D%5Cright%29%3D%5Clog_6%5Cleft%28%5Cfrac%7B1%7D%7B6%5E2%7D%5Cright%29)
![\log_6\left(\frac{1}{36}\right)=\log_6\left(6^{-2}\right)](https://tex.z-dn.net/?f=%5Clog_6%5Cleft%28%5Cfrac%7B1%7D%7B36%7D%5Cright%29%3D%5Clog_6%5Cleft%286%5E%7B-2%7D%5Cright%29)
![\log_6\left(\frac{1}{36}\right)=-2*\log_6\left(6\right)](https://tex.z-dn.net/?f=%5Clog_6%5Cleft%28%5Cfrac%7B1%7D%7B36%7D%5Cright%29%3D-2%2A%5Clog_6%5Cleft%286%5Cright%29)
Use log rule 1 (see above)
![\log_6\left(\frac{1}{36}\right)=-2*1](https://tex.z-dn.net/?f=%5Clog_6%5Cleft%28%5Cfrac%7B1%7D%7B36%7D%5Cright%29%3D-2%2A1)
Use log rule 2 (see above)
This means that the given expression simplifies to
-2You can use a calculator to type in "log(1/36)/log(6)" without quotes and you should get
-2 as the answer